PENGARUH PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KETERIKATAN KARYAWAN DAN PERILAKU KERJA PROAKTIF SEBAGAI VARIABEL INTERVENING (Studi pada PT Kereta Api Indonesia (Persero) Daop IV Semarang) - Aghnia Nabila, Hasna; Ratnawati, Intan (Diponegoro Journal of Management, 2020)
This study aims to analyze the influence of perceived organizational support on employee performance through employee engagement and proactive work behavior as mediators in one of the public companies in Semarang, namely PT Kereta Api Indonesia (Persero) Daop IV Semarang. This study uses data sources from primary data through the distribution of research questionnaires, and secondary data through journals, books, and relevant data obtained from the company. The samples of this reasearch is employees of PT Kereta Api Indonesia (Persero) Daop IV Semarang. The method used in this research is purposive sampling. The data analysis technique used in this study is Partial Least Square with Smart PLS 3.2.9 application to find out the path coefficient, and direct or indirect effects of exogenous variables on endogenous variables. This results of this study show how perceived organizational support has a positive effect on employee performance, employee engagement has a positive effect on employee performance, proactive work behavior has a positive effect on employee performance. This study also shows that the influence of employee engagement and proactive work behavior variables as mediators between perceived organizational support on employee performance where proactive work behavior has the bigger role as the intervening.